Effect of Tempeh Flour Supplementation During Pregnancy In Wistar Rats With Limited Diet - Wibowo, Joko Wahyu (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
Free radicals are formed in the body as a by-product of an aerobic respiration. During pregnancy, the increase in free radicals potentially causes structural and functional damages to fetus. Tempeh is originally from Indonesia having various nutrition inclding vitamin, mineral and isoflaphon serving as antioxidhant having potential to reduce and improve DNA damage. This study was aimed to investigate the effect of tempeh flour suplementation during pregnancy on Glutathione peroxides (GPx) and Malondetaldehyde (MDA) as an indicator of lipid peroxide in the offspings. In this experimental study, 20 pregnant female wistar rats were devided into four groups of 5 rats each to receive one of the following treatment :10 g standard diet/rat/d, 10 g/rat/d of standard diet and tempeh flour 1. g//d, 10 g/d of standard diet and tempeh flour 2g/d, standard diet of 10 g/d and 1g of egg/d. And aquades ad libitum. During nursing period (until 1 month) the rats were fed 10 g/100gBB/d normal diet, after weining they were supplemented with a diet of high in saturated fat for 4 weeks for each group. The Mean of litter size was 1: 9.33 with mean of BW 4.93 g, group II:6.17 with BW of 5.32, group III: 5.17 with BW of 5.33, group IV: 6.33 with BW: 5.01. Means of GPx for the four groups were 22.38 U/mg, 28.94 U/mg, 38.59 U/mg, 16.98 U/mg respectively. The mean of MDA for the four groups were 11.07 nmol/mg, 9.89 nmol/mg, 10.06 nmol/mg and 12.25 nmol/mg respectively. There was a significant difference in GPx and MDA (p=0.00). In conclusion tempeh flour had an effect on the level of GPx and MDA in rats with limited diet during pregnancy.